Small molecule inhibitors of IL-1R1/IL-1β interaction identified via transfer machine learning QSAR modelling - Pirzada, Rameez Hassan; Yasmeen, Farzana; Haseeb, Muhammad; Javaid, Nasir; Kim, Eunha; Choi, Sangdun (International Journal of Biological Macromolecules, 2024)
The human interleukin-1 receptor I (IL-1R1) is a cytokine receptor recognized by interleukin 1β (IL-1β), among other cytokines. Over activation of IL-1R1 has been implicated in various inflammatory conditions. This research aims to identify small-molecule inhibitors targeting the hIL1R1/IL1β interaction, employing a multi-task transfer learning approach for quantitative structure-activity relationship (QSAR) modelling. A comprehensive bioactivity dataset from functionally related proteins was utilised to build a robust ensemble machine learning model for predicting IC50 values against the target protein. Despite the availability of antibody-based therapies, the absence of orally available small-molecule inhibitors necessitates their development. By combining model predictions with docking and simulation approaches, the interleukin-1 receptor inhibitor (IRI-1) emerged as a lead compound. It potently inhibited human IL1-R1 with micromolar activity in THP-1 and Saos-2 cells and demonstrated good biocompatibility. Western blot analysis revealed that IRI-1 inhibits IL-1β-mediated phosphorylation of IL1-R1, JNK, IRAK-4, and ERK in THP-1 cells. Furthermore, molecular dynamics simulations confirmed the structural stability of the protein-ligand complexes. This study highlights the effectiveness of multi-task transfer learning approaches for building robust QSAR models against novel proteins or those with limited bioactivity data, such as hIL-1β/IL-1R1 protein.
Keywords: Dynamics simulation; Interleukin-1 receptor; Interleukin1; Molecular dynamic simulation; Multi tasks; Multi-task transfer learning; Quantitative structure activity relationship; Small-molecule inhibitors; Task transfer; Transfer learning; Humans; Interleukin-1beta; Machine Learning; Molecular Docking Simulation; Molecular Dynamics Simulation; Protein Binding; Quantitative Structure-Activity Relationship; Receptors, Interleukin-1 Type I; Small Molecule Libraries; Interleukin-1 receptor; Molecular dynamics simulation; Multi-task transfer learning; Quantitative structure-activity relationship